Studi Eksperimental Pengaruh Variasi Deflektor Pelat Lengkung terhadap Performa Turbin Air Savonius Sumbu Vertikal Dua Sudu - Sugeng Imar Fauzil (Infotekmesin, 2022)
The Savonius turbine has a simple construction making it easy to build. The weakness of the conventional Savonius turbine is that there is a negative torque due to the presence of blades that are opposite to the flow direction. Negative torque can be reduced by placing a curved plate at the front of the turbine. The purpose of this study is to analyze the use of a curved plate deflector for the performance of a two-blade Savonius vertical axis air turbine. The research was conducted by varying the curvature of the deflector, namely 1/4 circle, 3/8 circle and 1/2 circle experimentally. The test results show that the addition of a curved plate deflector improves turbine performance compared to without using a deflector. Of the three variations of the deflector, the 1/4 circle deflector has the highest performance with a power generated of 0.266 Watt and a power coefficient of 0.169 at 113 rpm.